Active Flexible Films for Food Packaging: A Review - Azevedo, Ana G. (2022)
Active food packaging is a dynamic area where the scientific community and industry have been trying to find new strategies to produce innovative packaging that is economically viable and compatible with conventional production processes. The materials used to develop active packaging can be organized into scavenging and emitting materials, and based on organic and inorganic materials. However, the incorporation of these materials in polymer-based flexible packaging is not always straightforward. The challenges to be faced are mainly related to active agents' sensitivity to high temperatures or difficulties in dispersing them in the high viscosity polymer matrix. This review provides an overview of methodologies and processes used in the production of active packaging, particularly for the production of active flexible films at the industrial level. The direct incorporation of active agents in polymer films is presented, focusing on the processing conditions and their effect on the active agent, and final application of the packaging material. Moreover, the incorporation of active agents by coating technologies and supercritical impregnation are presented. Finally, the use of carriers to help the incorporation of active agents and several methodologies is discussed. This review aims to guide academic and industrial researchers in the development of active flexible packaging, namely in the selection of the materials, methodologies, and process conditions.